Discovery Learning with the Solar System Scope Application to Enhance Learning in Middle School Students - Atika Zahara; Selly Feranie; Nanang Winarno; Nurhadi Siswontoro (Journal of Science Learning, 2020)
In education, “Industrial Revolution 4.0” refers to utilizing technology to present students with complex situations that will develop their critical thinking and problem-solving skills. The use of technology in the science curriculum should be designed according to established learning models. This study aimed to investigate the effect of implementing a discovery learning model, supported by the Solar System Scope computer application, on the ability of students to master essential concepts. This research used a One-Group Pre-test-Post-test design. Participants were 31 7th-grade students at one school in Bandung, Indonesia. The results showed a medium enhancement of concept mastery in students from pre-test to post-test (N-Gain=0.48). No gender difference in outcomes after the implementation of discovery learning with the Solar System Scope application was found. Based on these results, discovery learning supported by the Solar System Scope application could be an alternative teaching approach to enhance students' skills in mastering concepts.